2019
DOI: 10.1590/s2179-975x9317
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of aquatic macrophytes along depth gradients in Lajeado Reservoir, Tocantins River, Brazil

Abstract: Aim The present study investigated the diversity of aquatic macrophytes in the littoral zone of Lajeado Reservoir, Tocantins River. We characterized spatial variations in species richness, composition and abundance along depth gradients. Methods Macrophyte sampling occurred at the end of the dry season (September and October 2014) in four sites of the reservoir. We established transects perpendicular to the shoreline, each 25 m long, divided in 3 sections (plots of 5 x 5 m). Results In total, we recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Cichla species have been reported to rapidly colonize, and undergo population expansion, within dammed sections of rivers (Santos, 1995;Santos & Oliveira Jr., 1999). This is likely because they will readily consume a wide variety of fish species (Fugi, Luz-Agostinho, & Agostinho, 2008;Novaes, Caramaschi, & Winemiller, 2004;Williams, Winemiller, Taphorn, & Balbas, 1998).…”
Section: Study Taxa (Ecology)mentioning
confidence: 99%
See 1 more Smart Citation
“…Cichla species have been reported to rapidly colonize, and undergo population expansion, within dammed sections of rivers (Santos, 1995;Santos & Oliveira Jr., 1999). This is likely because they will readily consume a wide variety of fish species (Fugi, Luz-Agostinho, & Agostinho, 2008;Novaes, Caramaschi, & Winemiller, 2004;Williams, Winemiller, Taphorn, & Balbas, 1998).…”
Section: Study Taxa (Ecology)mentioning
confidence: 99%
“…Further, while cannibalism is a common phenomenon in this genus (e.g., C. monoculus, C. kelberi), it has been reported to occur more frequently in systems affected by dam operation (Novaes et al, 2004;Rosemara Fugi et al, 2008).…”
Section: Study Taxa (Ecology)mentioning
confidence: 99%
“…According to the above results and discussions from stomach content analysis (SCA) of H. macrolepidota and C. ocellaris it can be hypothesized that 1) the foraging activities of the NIS species C. ocellaris may cause diet inadequacy in the ecosystem for H. macrolepidota; 2) the predatory and violent behavior of C. ocellaris may resist H. macrolepidota to become more dynamic and lively to catch the prey. However, both of the hypotheses were preliminary predictions and expectations from an ecosystem consisting of predatory NIS fishes, especially Bass fishes [28], and need to be assessed further.…”
Section: Diet Consumption Frequency and Foraging Performancementioning
confidence: 98%
“…The primary goal of papers about community ecology (the second most important theme) is to explain patterns in species distributions, a topic well described by Chico in his seminal books mentioned earlier. The substitution of life forms across a depth gradient is one of the first known patterns of aquatic macrophyte community organization (e.g., Noleto et al 2019). Eugene Warming, the so-called 'father of Plant Ecology', called attention to such macrophyte zonation pattern in 'Lagoa Santa' (a lake situated in Central Brazil) in his book published in 1892 ("Lagoa Santa.…”
Section: Community Ecologymentioning
confidence: 99%
“…In general, the excessive growth of macrophytes, as stated long ago by Cook (1993), is a symptom rather than the cause of problems and, therefore, aquatic macrophytes are reliable indicators of the effects of several anthropogenic activities (e.g., eutrophication and river regulation). Accordingly, our review found, for example, several studies on macrophyte communities in reservoirs (Bini et al 1999, Noleto et al 2019, and focused on the effects of invasive species on native communities (Bora et al 2020, Lolis et al 2020.…”
Section: Community Ecologymentioning
confidence: 99%